Tool Used to Assess Co-Benefits of Nature-Based Solutions in Urban Ecosystems for Human Wellbeing: Second Validation via Measurement Application - Karmele Herranz-Pascual; Paula Anchustegui; Carolina Cantergiani; Ioseba Iraurgi (Land)
In recent years, nature-based solutions have been used in urban regeneration interventions to improve the adaptation and resilience of these places, contributing to improved environmental quality and cultural ecosystem functions, including people’s physiological, social, and mental health and wellbeing. However, when it comes to the assessment of psychological wellbeing and social benefits (psychosocial co-benefits), the existing evidence is still limited. To contribute to the advancement of knowledge on nature’s contribution to people in relation to this type of benefit, it is necessary for us to develop and test assessment tools to contribute to the development of a robust nature-based solutions monitoring framework. In this paper, the second phase of the validation of a psychosocial co-benefit assessment tool for nature-based urban interventions is presented. This tool is structured around two dimensions: the perceived health and wellbeing and social co-benefits. The first validation was carried out with experts using the Delphi method. The second validation presented in this paper was based on a sample of users, evaluating a set of eight urban spaces at different levels of naturalisation and openness. The results indicate that the tool is sensitive to the differences in naturalisation and openness in the public urban places analysed. The most relevant contextual variables to explain the psychosocial co-benefits are openness, the surfaces covered by tree branches, the water surface area, and naturalisation.